2015
DOI: 10.1073/pnas.1419704112
|View full text |Cite
|
Sign up to set email alerts
|

Rate of language evolution is affected by population size

Abstract: The effect of population size on patterns and rates of language evolution is controversial. Do languages with larger speaker populations change faster due to a greater capacity for innovation, or do smaller populations change faster due to more efficient diffusion of innovations? Do smaller populations suffer greater loss of language elements through founder effects or drift, or do languages with more speakers lose features due to a process of simplification? Revealing the influence of population size on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 47 publications
(73 reference statements)
11
101
0
Order By: Relevance
“…In addition to the destiny of other species, human population size also influences our own cultural and genetic evolution. Large pools of interacting individuals can create and maintain adaptive skills, as well as phonological variation, more effectively than small populations, and they are also capable of faster cumulative cultural evolution (3)(4)(5). A decrease in population size may even result in a loss of complex cultural traits (6).…”
mentioning
confidence: 99%
“…In addition to the destiny of other species, human population size also influences our own cultural and genetic evolution. Large pools of interacting individuals can create and maintain adaptive skills, as well as phonological variation, more effectively than small populations, and they are also capable of faster cumulative cultural evolution (3)(4)(5). A decrease in population size may even result in a loss of complex cultural traits (6).…”
mentioning
confidence: 99%
“…Bromham et al (2015) applied this technique to 20 Polynesian languages and found a correlation between speaker population size and rates of linguistic change. Specifically, their results conformed to the expectations of population genetics, as large populations gained words faster while small populations lost words faster.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, their results conformed to the expectations of population genetics, as large populations gained words faster while small populations lost words faster. However, Bromham et al (2015) only investigated a restricted dataset of 20 Polynesian languages, a small subgroup of the Austronesian language family (Hammarström et al 2014). They argued that Polynesian languages were an ideal study group as they are well documented, and spoken on isolated islands that were sequentially founded as humans expanded across the Pacific Ocean (Gray et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations